Analisis Korelasi Tingkah Laku Seksual terhadap Produksi Spermatozoa Sapi Simmental di Balai Inseminasi Buatan Provinsi NTB - Dwi Sartika, Diana; Nealma, Samuyus; Reza Jatnika, Ahmad (BIOMARAS : Journal of Life Science and Technology, 2025)
This study aims to determine the Relationship of Sexual Behavior to Sperm Production of Simmental Cattle in BIBD Banyumulek, West Nusa Tenggara Province. Evaluation of semen quality was carried out macroscopically including the number of spermatozoa volume and microscopically including motility and spermatozoa concentration. The analytical method used was a descriptive method and was analyzed using person correlation analysis. The results showed that the highest sexual behavior value (erection time) was found in the Surya 2 bull 28.44 ± 25.01 seconds, while the highest sexual behavior (reaction time) was found in the Surya 2 bull with a duration of 33.35 ± 23.88 seconds and the highest sexual behavior (ejaculation time) was found in the Surya 2 bull with a duration of 36.88 ± 10.50 seconds. The highest average value of Spermatozoa Production (TS) was found in the male Surya 2 63.78±42.69 (x10ml) and the highest average value of Total Motile Spermatozoa (TSM) was found in the male Surya 2 3856.69±2654.59 (x10ml). the results of the analysis showed an influence with a sig value (p<0,05) of sexual behavior on TS there was an influence with a sig value (0,04) and (0,02) in Simental cattle. Sexual behavior on TSM (p>0,05) there was no influence with a sig value (0,10) in Simental cattle at the regional artificial Insemination Center of West Nusa Tenggara province